A CASE REPORT: RISK OF ELECTRIC INJURY ON DELAYED INITIAL TREATMENT - Elfiah, Ulfa; Suryani, Dissa Yulianita (Universitas Airlangga, 2019)
Highlights: Electric injuries are aggressive burns that can lead to severe tissue necrosis, rhabdomyolysis, and a range of complications, including acute kidney injury (AKI). A multidisciplinary approach and early identification of potential complications in electric injury cases are crucial for reducing the risk of Acute Kidney Injury (AKI) and improving patient outcomes. Abstract: Introduction: Electric Injury is a very aggressive burn injury with severe functional and aesthetic consequences caused by progressive and prolonged tissue necrosis. Necrosis that attacks the skeletal muscle can lead to rhabdomyolysis which results in complications if not treated properly. Case Illustration: A complicated case of electric injury in Dr. Soebandi Jember General Hospital, a 26 years old man came to the emergency room with complaints of severe shortness of breath and urinary disorders. The patient had a history of having an electric shock in his right hand when turning on the fan a week prior of admission. The examination showed that the patient had bilateral pulmonary effusion, generalized edema and acute tubular necrosis (ATN) which was characterized by oliguria and even anuria accompanied by hematuria. Other symptoms experienced by patients are anterior uveitis, subconjunctival hemorrhage, and hematemesis. Discussion: Electric injuries can have a wide range of effects on the body, and their management requires a multidisciplinary approach to address the various complications that may arise. Treatment of electric injuries often involves various surgical procedures, including skin grafts, flaps, or amputation, depending on the severity of the injury. Conclusions: Early identification of potential complications in electric injury cases and effective patient follow-up can reduce the risk of Acute Kidney Injury (AKI) occurrence in patients with electric injuries.